2021
DOI: 10.1007/s00467-021-05111-x
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir use in children with COVID-19 and acute kidney injury: is it safe?

Abstract: Background The rising number of infections due to Severe Acute Respiratory Syndrome Coronavirus-2 (popularly known as COVID-19) has brought to the fore new antiviral drugs as possible treatments, including favipiravir. However, there is currently no data regarding the safety of this drug in patients with kidney impairment. The aim of this paper, therefore, is to share our experience of the use of favipiravir in pediatric patients affected by COVID-19 with any degree of kidney impairment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
14
0
3
Order By: Relevance
“…Favipiravir was used with no dose adjustment and no measurement of plasma levels by Ozsurekci and colleagues in two out of 11 critically ill children diagnosed with the multisystem inflammatory syndrome in children (MIS-C) after Covid-19 infection, on CKRT, with eGFR <30 ml/min/1.73 m 2 ( 35 ). Doses followed weight as per the recommendations for Ebola ( Table 9 ), without any dose adjustment for kidney dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…Favipiravir was used with no dose adjustment and no measurement of plasma levels by Ozsurekci and colleagues in two out of 11 critically ill children diagnosed with the multisystem inflammatory syndrome in children (MIS-C) after Covid-19 infection, on CKRT, with eGFR <30 ml/min/1.73 m 2 ( 35 ). Doses followed weight as per the recommendations for Ebola ( Table 9 ), without any dose adjustment for kidney dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…There are also first‐time or re‐emerging viral infections for which effective drug or vaccine treatments are not available (Furuta et al, 2017). Nowadays, the most obvious example of this situation is COVID‐19 and favipiravir is used effectively in its treatment by some countries (Furuta et al, 2017; Ozsurekci et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The main elimination route of the drug is via the kidneys, and inactive metabolites produced by aldehyde oxidase and xanthine oxidase are excreted in the urine. It has been reported that its side effects have a safer profile than most antiviral agents (Ozsurekci et al, 2021). However, its use is contraindicated in patients with severe hepatic and renal impairment, hypersensitivity, and hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some warnings have been issued, and adverse reactions, including bone marrow suppression, hepatotoxicity, and hypersensitivity reaction, were reported (12). and efficacy of favipiravir in the pediatric population (13,14) and no specific reported dosing recommendation for the pediatric population, the used dosage was derived from the limited data for this drug in the treatment of Ebola in children.…”
Section: Introductionmentioning
confidence: 99%